Physical Literacy Research Trends In Children In Indonesia: Analysis Using Scopus Database - Fahri, Achmad Syakur; Lubay, Lukmannul Haqim; Nugroho, Wildan Alfia; S, Adi; Malik, Arief Abdul; Gustian, Uray; Pambudhi, Yudhi Teguh (STAMINA, 2025)
This study aims to provide an overview of the state of physical literacy research in Indonesia and contribute to the global discussion on the development of physical literacy in children. It focuses on: (1) the prevailing themes and focus areas in physical literacy research related to children in Indonesia, (2) how these themes have evolved over time, (3) the dominant methodologies used in these studies, and (4) the gaps and areas identified for future research. The Scopus database was used to select articles containing information on the implementation and impact of physical literacy on children in Indonesia. The search followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. After applying exclusion criteria, only seven articles qualified for in-depth analysis. A review of the literature reveals that the development of physical literacy in children requires a planned approach involving a learning model that integrates fundamental motor skills. Evaluation instruments for physical literacy are also crucial, yet only a few adapted instruments have been tested. Moreover, there is currently no specific framework for physical literacy in Indonesia, despite its reliance on the ecological context of a region. This review identifies that research on physical literacy in Indonesia, particularly for children, remains very limited. Considering the critical role of early childhood development for later life, frameworks, assessment instruments, learning models, and programs to enhance physical literacy for children in Indonesia are notably scarce. Future research is expected to focus on these areas